Gitlane: Where the Moon Sicle Strikes – On the Edge of Time at Elandsdoorn (Nordic Journal of African Studies, 1999)
Ancient trade between gold producing southern Africa and gold consuming India shaped the people and the history of the BoPedi country in Mpumalanga and Northern Provinces of South Africa. The culture and religious beliefs of the BaPedi and of the Quena (Hottentots) who lived here before the Bantu-speakers arrived, reflect this history. Stone structures build during that period of Indo-African interaction reflect the religious cosmology of ancient Dravidian India and this enables us to understand them. Time was a factor that mattered in the context of the resulting Indo-African culture. They measured it precisely. A Moon Sickle on the hill south of the Gitlane River was one of their horological instruments. It measured the time of death for the community of monks and aged recluses in a nearby cave monastery.